EP.FRI.306 The Mule who took us for a ride. (28th October 2021) - El-Abbassy, Islam; Perakath, Benjamin
Abstract: Introduction: Foreign body ingestion is not uncommon in patients with mental disorders, alcohol intoxication and for purposes of drug trafficking. Small objects pass spontaneously; however, larger ones may get stuck in the oesophagus, stomach or at narrow areas of the bowel. "Body packers" is a term used to describe persons who swallow or insert drug-filled packets into a body cavity. They are also called "swallowers", "internal carriers" "couriers" or "mules". Case report: We report a 37 year old previous drug abuser who presented with dysphagia. Upper GI endoscopy showed an oblong foreign body covered in plastic in the lower oesophagus. This could not be extracted and hence was pushed into the stomach. Three weeks later, he presented with bowel obstruction that was shown on abdominal radiograph and confirmed by CT indicating multiple dilated small bowel loops with a transition point in the terminal ileum where the ingested package was identified. The package was then removed through a longitudinal enterotomy.  Conclusion: Ingested foreign bodies causing dysphagia should ideally be extracted endoscopically. If not possible, then a watch and wait policy may be justified. While most ingested objects pass spontaneously, unusual and larger ones may require surgical extraction. The contents, nature and reason for ingesting this strange object remain a mystery. With history of drug abuse and the consistent denial of knowingly swallowing that object, we can only conclude that the patient was trying to transport an illicit drug in the packet. Keywords: Foreign body ingestion, bowel obstruction, body packers.